THE VOCABULARY TEACHING AND VOCABULARY LEARNING: PERCEPTION, STRATEGIES, AND INFLUENCES ON STUDENTS VOCABULARY MASTERY - Asyiah, Dewi Nur (Jurnal Bahasa Lingua Scientia, 2017)
Vocabulary plays pivotal role in foreign language learning. However, vocabulary teaching and vocabulary learning in TEFL seems to be neglected. The study was aimed to investigate how vocabulary teaching and learning are perceived by teacher and students, strategies to teach and learn the vocabulary, and also influences of studentsâ vocabulary learning strategy on their vocabulary mastery. Accordingly, a mix method design was employed to one English teacher and 30 junior high school students to reveal the issues being investigated. The findings showed that both teacher and students have positive response on vocabulary teaching and learning. Concerning strategies, it was found that teacher mostly employed Fully-contextual strategy, meanwhile Determination and Metacognitive strategy were found as the most favored VLS chosen by students. The study also confirmed that there is a significant relationship between studentsâ vocabulary learning strategy and their vocabulary mastery (r-value Discovery = .023 and r-value Consolidating = .000, p<.05). It is recommended for EFL teachers to give a bigger portion to vocabulary in the EFL teaching and to teach vocabulary using the combination of fully-contextual and de-contextual strategy. It is also suggested to introduce students to various kinds of vocabulary learning strategies. Â